Pengembangan modul dengan menggunakan model pembelajaran discovery learning untuk meningkatkan hasil belajar - Abdillah, Abdillah (JP3M: JURNAL PEMIKIRAN DAN PENELITIAN PENDIDIKAN MATEMATIKA, 2018)
This research is a development research aimed at describing product quality in terms of validity, practicality, and effectiveness. The procedure in this development uses a 4-D development model, namely: Define, Design, Develop, and Disseminate. But in this study only includes Define (definition), Design (planning), Develop (development). The product developed in the form of a module in the material system of two-variable linear equations for class VIII students by taking the steps in Discovery Learning. The instruments used in this study are module assessment sheets by experts to measure module validity, student response questionnaires to measure module practicality, and learning outcomes tests to measure the effectiveness of module use.